2005
DOI: 10.3928/1542-8877-20050701-15
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Findings After an Intravitreal Injection of Bevacizumab (Avastin®) for Macular Edema From Central Retinal Vein Occlusion

Abstract: Abstract. To determine whether bevacizumab could improve visual acuity and optical coherence tomography outcomes in a patient with macular edema from central retinal vein occlusion, an intravitreal injection of bevacizumab (1.0 mg) was given. Prior intravitreal injections of triamcinolone acetonide resulted in vision improvement but worsening cataract and borderline glaucoma. Wthin 1 week of the bevacizumab injection, visual acuity improved from 20/200 to 20/50 and optical coherence tomography revealed resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
206
0
12

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(224 citation statements)
references
References 12 publications
6
206
0
12
Order By: Relevance
“…After its excellent inhibitory effects on neovascularization in various retinal diseases were revealed [1,2,5,14,17,18], its inhibitory effects on corneal neovascularization have been studied recently. After the inhibitory effects of bevacizumab on corneal neovascularization were first reported through the subconjunctival injection of bevacizumab into corneal neovascularization of rats [4] and humans [10] respectively, the inhibitory effects of bevacizumab on corneal neovascularization of rats [13] and humans [9] respectively through eye drops of bevacizumab were reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After its excellent inhibitory effects on neovascularization in various retinal diseases were revealed [1,2,5,14,17,18], its inhibitory effects on corneal neovascularization have been studied recently. After the inhibitory effects of bevacizumab on corneal neovascularization were first reported through the subconjunctival injection of bevacizumab into corneal neovascularization of rats [4] and humans [10] respectively, the inhibitory effects of bevacizumab on corneal neovascularization of rats [13] and humans [9] respectively through eye drops of bevacizumab were reported.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that intravenous or intravitreal injection of bevacizumab has particularly good results in patients with exudative age-related macular degeneration [2,5,14]. In addition, the intravitreal injection of bevacizumab achieved reduced neovascularization of the retina and iris in patients with proliferative diabetic retinopathy [1,18] and reduced edema in patients with central retinal vein occlusion accompanied by macular edema [17].…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have demonstrated usefulness of the intravitreal injection of the drug in the treatment of macular edema secondary to various causes [8,[11][12][13]. The effect of intravitreal bevacizumab for BRVO also showed promising functional and anatomic results [7,8,[14][15][16]. However, although the injection usually results in clinical improvement, expressed as a reduction in macular thickness, visual acuity does not improve in many patients.…”
Section: Introductionmentioning
confidence: 97%
“…The molecules can penetrate the retina, and they are also transported into the retinal pigment epithelium, the choroid, and, in particular, into the photoreceptor outer segments after an intravitreal injection [6]. Clinically, bevacizumab has been administered intravitreally in VEGF-mediated diseases, such as choroidal neovascularization, central retinal occlusion, proliferative diabetic retinopathy, and other retinal diseases [7][8][9][10]. Many reports suggest that bevacizumab is useful in helping to reduce and ultimately cause the disappearance of newly formed abnormal vessels [7,8,11,12].…”
Section: Introductionmentioning
confidence: 99%